PKBI: Aktor Intermediary dan Gerakan Sosial Baru - - Haryanto; Siti Mauliana Hairini; Abu Bakar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2013)
In contemporary political developments, various measures have been carried out by the intermediary actor in the role and function as a state society relations. This article gives an overview of how the strategy undertaken by the intermediary actor through new social movement approach. It concludes that the New Social Movement not only be found in Europe and America, but also at the local level in Indonesia.